A comparative radiation analysis of reconfigurable memory technologies: FinFET versus bulk CMOS. (November 2022) - Azimi, S.; De Sio, C.; Portaluri, A.; Rizzieri, D.; Sterpone, L.
Abstract: This work describes a comparative radiation reliability analysis between two reconfigurable devices with different manufacturing technology: 28 nm CMOS-based and 16 nm FinFET based FPGAs. The analysis is based on a proton radiation test campaign performed at the PSI radiation facility. As application circuit, a multi-core computational engine was implemented on each one of the reconfigurable devices. The radiation sensitivity has been reported in terms of the SEU cross-section of the configuration memory bits. Results have shown a higher sensitivity of 28 nm CMOS with respect to 16 nm FinFET. Moreover, a detailed comparison of detected Single Event Multiple Upsets (SEMUs) clusters for both technology is reported.